Cellular Multihop Networks: State of the Art - Sutanto Tarsono, Teddy; Umbu Tana Amah, Aditya (Institute of Research and Community Outreach, 2004)
This paper presents the summary of some research in the area of cellular multihop networks that contains the improvement in network performance also the difficulties and the complexities of the networks. The combination of two different networks, mobile cellular networks and WLAN ad hoc networks will be presented. The main purpose of the combination is to minimize the weaknesses of both network types when they are deployed separately. By having this combination then it is possible to provide higher mobility for WLAN ad hoc networks user and higher data transfer rate for cellular network users in multimedia applications. The cellular multihop networks will reduce blocking probability, balance the cells load and increase the network capacities. Although there are improvement on the performance of the combine networks, but there are additional aspects that should be considered seriously, especially for WLAN ad hoc users. Authentication, Authorization and Accounting (AAA) functions, the dynamic routing and relay path discovery, maintenance and security issues are aspects to be considered for cellular multihop network. Abstract in Bahasa Indonesia : Paper ini merupakan ringkasan dari beberapa penelitian di bidang cellular multihop networks dengan pemaparan pada peningkatan unjuk kerja jaringan dan kesulitan serta kompleksitas jaringan. Penggabungan dari dua jaringan yang berbeda antara jaringan Mobile Cellular dengan jaringan WLAN ad hoc akan dipaparkan. Tujuan utama dari penggabungan ini adalah untuk meminimalkan kekurangan kedua jaringan saat diimplementasikan secara terpisah. Penggabungan ini memungkinkan pergerakan yang lebih luas bagi pengguna jaringan WLAN ad hoc dan laju transfer data yang tinggi untuk pengguna jaringan seluler. Peningkatan lainnya adalah adanya pengurangqn probabilitas blocking, penyeimbangan beban sel-sel dan peningkatan kapasitas jaringan. Walau terdapat peningkatan pada unjuk kerja melalui penggabungan kedua sistem tersebut, terdapat pula aspek-aspek yang tetap harus diperhatikan secara serius, terutama bagi pengguna jaringan WLAN ad hoc. Fungsi Authentication, Authorization and Accounting (AAA), dynamic routing dan relay path discovery, pemeliharaan serta keamanan merupakan aspek-aspek yang harus diperhitungkan pada jaringan Cellular Multihop. Kata kunci : cellular networks, ad hoc networks, multihop networks, WLAN, routing.